1993
DOI: 10.1007/bf00004585
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and comparison of biological properties of recombinant carp (Cyprinus carpio) growth hormone and its Cys-123 to Ala mutant

Abstract: Carp growth hormone (cGH) cDNA, in which Cys-123 was mutated to Ala, was prepared, transferred to the expression vector, expressed in Escherichia coli and the mutant was purified to homogeneity. The mutation only slightly improved yield of the monomeric fraction, indicating that Cys-123 is not involved in improper refolding. As compared to cGH, the mutant (cGH-C123A) exhibited lower binding affinity toward homologous liver receptors and lower bioactivity in a 3T3-F442A preadipocyte bioassay despite the fact th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The rcGH used in the present study contains an extra cysteine residue at position 123, as found in the common carp (Fine et al 1993, Law et al 1996. This cysteine does not appear to be directly involved in binding of rcGH to the receptor (Fine et al 1993). Goldfish also possess cDNAs for two GHs; one has cysteine at position 123, whereas this position in the other GH contains a serine (Mahmoud et al 1996).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The rcGH used in the present study contains an extra cysteine residue at position 123, as found in the common carp (Fine et al 1993, Law et al 1996. This cysteine does not appear to be directly involved in binding of rcGH to the receptor (Fine et al 1993). Goldfish also possess cDNAs for two GHs; one has cysteine at position 123, whereas this position in the other GH contains a serine (Mahmoud et al 1996).…”
Section: Discussionmentioning
confidence: 77%
“…The rcGH used in the present study contains an extra cysteine residue at position 123, as found in the common carp (Fine et al 1993, Law et al 1996. This cysteine does not appear to be directly involved in binding of rcGH to the receptor (Fine et al 1993).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This latter method does not provide information on whether the purified hormone exists as a monomer or as a mixture of monomers, noncovalent dimers, or oligomers that cannot be identified by SDS-PAGE (11). In contrast, the reports from our laboratory regarding the preparation of three, to date prepared, fish GHs (12)(13)(14)(15) or other proteins (11,16 -22) are always accompanied by a determination of monomer content using a sensitive gel-filtration method. In many cases (12,13,16 -20), we have shown that only the monomers are biologically active despite the other forms' apparent purity on an SDS-polyacrylamide gel or their ability to interact with antibodies.…”
mentioning
confidence: 74%
“…Another problem that may hamper the application of GH therapy is a lack of homologous hormones. Although heterologous GHs or related hormones, such as ruminant placental lactogen, have been found to be active in vivo (13,15,(25)(26)(27)(28)(29)(30)(31), their prolonged use may be problematic, as it may elicit an undesired immunological response. Therefore, preparation of homologous GH seems to be quite important.…”
mentioning
confidence: 99%